Jurnal Biology Education 2015 - Dasrieny Pratiwi (Jurnal Biology Education, 2015)
KEMAMPUAN CALON GURU BIOLOGI DALAM MENYUSUN RENCANA PEMBELAJARAN BERBASIS KURIKULUM 2013 1Dasrieny Pratiwi  2Agil LepiyantoUniversitas Muhammadiyah Metro Lampung ABSTRACTThe aim for this reseach is to get  the information about preservice abblity to construct the lesson plan base on kurikulum 2013.  About 12 lesson planwas an analissed according Samani’s instrument and reseach need.  For complited the data, this research using questionnaire for preservice whos to get subject microteaching TP. 2013/2014 at Universitas Muhammadiyah Metro.  The data was quantitative analisysis. Data shows about 50% preservice abbility is good category for construct lesson plan base on kurikulum 2013. And the syntax was on student centered.  Altought that, according questionnaire they admit that constructing the lesson plan make him is a verry dizzy activity, so that they (several) just download the same lesson plan from the internet that has a simmiliar topic. Keyword: lesson plan, kurikulum 2013